Pengaruh Psychological Well-Being dan Kepuasan Kerja Terhadap Stres Kerja Anggota Himpunan Penerjemah Indonesia - Nadhirotul Husnah Panggabean; Abdul Haris; Nefi Darmayanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research aims to determine the influence of psychological well-being and job satisfaction on job stress members of the association of Indonesian translators. This study used a quantitative method in which the sampling technique was through a simple random sampling technique where the subjects in this study amounted to 141 people. Data were collected using was a Likert scale consisting of three scales, namely the psychological well-being scale, job satisfaction scale, and work stress scale. The data analysis technique used multiple regression analysis. The results showed that there was be a significant effect between psychological well-being and job satisfaction on the work stress of HPI members. This is indicated by the coefficient F reg = 15.211 with p < 0.05, and the coefficient R = 0.425 with p < 0.05 and R2 = 0.181. The total contribution of these two variables was 18.1%, while the remaining was 81.9% is influenced by other factors on job stress. From the result of the study, it can be concluded that psychological well-being and job satisfaction jointly affect the work stress of the association of Indonesian translators